"Because you're worth it?" The taking and selling of transplantable organs. Issue 6 (26th May 2006) - Haddow, G
Abstract : In the UK, the legal processes underpinning the procurement system for cadaveric organs for transplantation and research after death are under review. The review originated after media reports of hospitals, such as Alder Hey and Bristol, retaining organs after death without the full, informed consent of relatives. The organ procurement systems for research and transplantation are separate and distinct, but given that legal change will be applicable to both, some have argued now is the time to introduce alternative organ transplant procurement systems such as presumed consent or incentive based schemes (despite inconclusive British and American research on the status of public attitudes). Findings are reported in this paper from qualitative and quantitative research undertaken in Scotland in order to ascertain the public acceptability of different procurement systems. Nineteen in depth interviews carried out with donor families about their experiences of donating the organs of the deceased covered their views of organ retention, presumed consent, and financial incentives. This led onto a representative interview survey of 1009 members of the Scottish public. The originality of the triangulated qualitative and quantitative study offers exploration of alternative organ procurement systems from different "sides of the fence". The findings suggest that the legal changes taking place are appropriate in clarifying the role of the family but can go further in strengthening the choice of the individual to donate.